2001
DOI: 10.1046/j.1537-2995.2001.41091120.x
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of human herpes virus 8 antibody in populations at high or low risk of transfusion, graft, or sexual transmission of viruses

Abstract: The sexual route appears to be the main route of HHV-8 transmission; bloodborne transmission of HHV-8, if it exists, is rare. In contrast, organ transplantation recipients might be exposed to HHV-8 transmission by the transplanted organ, which raises the issue of systematic screening of organ donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0
1

Year Published

2003
2003
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 27 publications
3
36
0
1
Order By: Relevance
“…The high frequency of iatrogenic KS in Saudi Arabia reflects the 7% endemic seroprevalence of KSHV in healthy Saudi donors or patients with non-KS malignancies (412). Interestingly, transplant-associated KS is seen predominantly in kidney allograft recipients and not other solid-organ or bone marrow transplant recipients (230); kidney recipients have a greater than two-fold-higher seroprevalence than those at low risk of KS in France (85). Although Andreoni et al found that 21.4% of liver recipients, but only 8.6% of kidney recipients, seroconverted for KSHV, the risk of KS was higher in the kidney transplant recipients.…”
Section: Iatrogenic Ksmentioning
confidence: 99%
“…The high frequency of iatrogenic KS in Saudi Arabia reflects the 7% endemic seroprevalence of KSHV in healthy Saudi donors or patients with non-KS malignancies (412). Interestingly, transplant-associated KS is seen predominantly in kidney allograft recipients and not other solid-organ or bone marrow transplant recipients (230); kidney recipients have a greater than two-fold-higher seroprevalence than those at low risk of KS in France (85). Although Andreoni et al found that 21.4% of liver recipients, but only 8.6% of kidney recipients, seroconverted for KSHV, the risk of KS was higher in the kidney transplant recipients.…”
Section: Iatrogenic Ksmentioning
confidence: 99%
“…[4][5][6][7][8][9] However, only a few studies have investigated risk factors for progression to KS among individuals coinfected with HIV and HHV-8.…”
mentioning
confidence: 99%
“…[1][2][3] Previous studies of acquired immunodeficiency syndrome (AIDS) patients have identified risk factors for infection with HHV-8, including sexual activity among homosexual men, intravenous drug use and blood transfusion. [4][5][6][7][8][9] However, only a few studies have investigated risk factors for progression to KS among individuals coinfected with HIV and HHV-8.…”
mentioning
confidence: 99%
“…The performance of these assays can be quite variable, and could account for the differences in seroprevalence reported in different studies (Pellett et al, 2003;Rabkin et al, 1998;Tedeschi et al, 2002). In North America and Northern and Western Europe, KSHV seroprevalence in adult general population or blood donors ranges from 0% to 8% (Challine et al, 2001;de Sanjose et al, 2002;Gambus et al, 2001;Gao et al, 1996b;Goedert et al, 1998;Lennette et al, 1996;Simpson et al, 1996). In these countries, the seroprevalence of KSHV in different risk groups mirrors the incidence of AIDS-KS, with a seroprevalence rate of between 25% and 50% among homosexual men.…”
Section: B Kshv Epidemiologymentioning
confidence: 99%